Influence of age on the behavior of dental pulp of dog teeth after capping with an adhesive system or calcium hydroxide - Mestrener, Sandra Rahal [UNESP]; Holland, Roberto [UNESP]; Dezan Junior, Eloi [UNESP] (Blackwell Munksgaard, 2003)
This study evaluated histomorphologically the influence of chronological age of the dog on the dental pulp-healing process after capping with the All Bond 2 system or with calcium hydroxide paste. The animals were divided according to age into young and adult groups. Class 5-type cavities were prepared, and the pulp was submitted to an exposure of a diameter of 0.5 mm. The pulp of the teeth was then protected with the adhesive system or with a calcium hydroxide paste. Sixty days after treatment, the results obtained with the adhesive system in the young group were significantly better than those in the adult group. With calcium hydroxide, the results were similar for both groups. The pulp treated with calcium hydroxide exhibited a complete hard tissue bridge and a pulp without inflammatory reaction, a fact not observed when the adhesive system was used. In conclusion, the chronological age of the pulp influenced the comparative results only for the adhesive system (P = 0.1), and the total results were better with calcium hydroxide than with the All Bond 2 system (P = 0.01).
Keywords: pulp capping; calcium hydroxide; adhesive system